A Study of the Role of Human Resource Functions in Talent Development Contributing to an Organization#x2019;s Business Growth in Today#x2019;s Knowledge and Innovation based Economy. Case Study #x2013; BICEC Cameroon (Global Journal of Management and Business Research, 2018)
This report aims at analysing the role of Human Resource functions in talent development contributing to an organization#x2019;s business growth in today#x2019;s knowledge and innovation based economy. For this purpose to be fully satisfied, the report focused on the following three human resource functions: selection, training and development, and job design and analysis which were then linked to talent management processes to analyse and evaluate their respective degree of significance vis-#xE0;-vis the company#x2019;s business growth. In order to provide practical examples and illustrations, the Cameroonian leading commercial bank, BICEC (International Bank of Cameroon for Savings and Credit) was designated as the report main case study together with other examples from other European companies as well. The results of the paper indicated that if company HR strategies (Selection, training and development, and job analysis and design) are in line with its talent management programme, it definitely impacts significantly on the company#x2019;s performance and growth.